Implementasi Metode Diferensiasi dalam Kurikulum Merdeka untuk Mengakomodasi Perbedaan Kemampuan Siswa Kelas XI di SMAN 1 Percut Sei Tuan - Tiarma Rokasih Sagala; Ester Susmaita Kaban; Vember Tri Rejeki Sitanggang; Andini Ridwana; Mirna Putri Aulia; Sri Rahma Haryanti; Sari Handayani Berutu; Rosmawati Harahap (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study describes the implementation of the differentiation method in the Independent Curriculum to accommodate differences in the abilities of grade XI students at SMAN 1 Percut Sei Tuan. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results show that teachers implement product differentiation by giving students the freedom to express their understanding according to their interests, learning styles, and readiness through the Discovery Learning model. Assessment is carried out using a flexible rubric that emphasizes core competencies. This method has proven effective in creating inclusive, meaningful learning that can optimize student potential.